2018
DOI: 10.1111/ele.13089
|View full text |Cite
|
Sign up to set email alerts
|

Transcending data gaps: a framework to reduce inferential errors in ecological analyses

Abstract: The analysis of functional diversity (FD) has gained increasing importance due to its generality and utility in ecology. In particular, patterns in the spatial distribution and temporal change of FD are being used to predict locations and functional groups that are immediately vulnerable to global changes. A major impediment to the accurate measurement of FD is the pervasiveness of missing data in trait datasets. While such prevalent data gaps can engender misleading inferences in FD analyses, we currently lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 90 publications
0
52
0
1
Order By: Relevance
“…Traits were simulated under a Brownian model of evolution, with a Gaussian distribution of values ranging from zero to 10 to mimic the distribution of real trait data on a logarithmic scale (a transformation often used in comparative studies). The impact of phylogenetic signal strength on imputation performance was already tested by Kim et al (2018) and Molina‐Venegas et al (2018); therefore, we standardized Pagel’s λ between the phylogeny and traits at approximately one. The response was simulated as a product of a trait, rather than through the phylogeny, and has a Gaussian distribution ranging from zero to 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traits were simulated under a Brownian model of evolution, with a Gaussian distribution of values ranging from zero to 10 to mimic the distribution of real trait data on a logarithmic scale (a transformation often used in comparative studies). The impact of phylogenetic signal strength on imputation performance was already tested by Kim et al (2018) and Molina‐Venegas et al (2018); therefore, we standardized Pagel’s λ between the phylogeny and traits at approximately one. The response was simulated as a product of a trait, rather than through the phylogeny, and has a Gaussian distribution ranging from zero to 10.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, correlations and phylogenetic information can be used to predict missing trait values more accurately (Penone et al, 2014; Swenson, 2014). Previous studies have suggested that imputation in ecological and evolutionary studies generally outperforms complete‐case analysis (Kim et al, 2018; Little & Rubin, 2002; Penone et al, 2014). However, imputation can only be successful if it accounts for the mechanism by which data are missing.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve complete species trait coverage, we imputed missing data using multivariate imputation with chained equations (MICE), based on functional (the transformed traits) and phylogenetic [the first 10 phylogenetic eigenvectors extracted from trees for birds (Prum et al, ) and mammals (Fritz, Bininda‐Emonds, & Purvis, )] relationships between species. MICE has been shown to have improved sample size and smaller error and bias than the data deletion approach and other multiple imputation approaches (Kim, Blomberg, & Pandolfi, ; Penone et al, ; Taugourdeau, Villerd, Plantureux, Huguenin‐Elie, & Amiaud, ). The data deletion approach was performed for comparative purposes (Supporting Information Appendix S4, Figure S4.1, Table S4.3).…”
Section: Methodsmentioning
confidence: 99%
“…The first 10 eigenvectors in our data represented 61% of the variation in the phylogenetic distances among seabirds. Phylogenetic data can improve the estimation of missing trait values in the imputation process (Kim et al, 2018;Swenson, 2014). This is because closely related species tend to be more similar to each other (Pagel, 1999) and many traits display high degrees of phylogenetic signal (Blomberg, Garland, & Ives, 2003).…”
Section: Multiple Imputationmentioning
confidence: 99%
“…Blomberg, & Pandolfi, 2018; Penone et al, 2014;Taugourdeau, Villerd, Plantureux, Huguenin- Elie, & Amiaud, 2014).…”
mentioning
confidence: 99%